WaaZam! Supporting creative play at a distance in customized video environments (Best Paper Nomination) - Hunter, Seth; Maes, Pattie; Tang, Anthony; Inkpen, Kori; Hessey, Sue (ACM CHI 2014, 2014)
We present the design, and evaluation of WaaZam, a video mediated communication system designed to support creative play in customized environments. Users can interact together in virtual environments composed of digital assets layered in 3D space. The goal of the project is to support creative play and increase social engagement during video sessions of geographically separated families. We try to understand the value of customization for individual families with children ages 6-12. We present interviews with creativity experts, a pilot study and a formal evaluation of families playing together in four conditions: separate windows, merged windows, digital play sets, and customized digital environments. We found that playing in the same video space enables new activities and increases social engagement for families. Customization allows families to modify scenes for their needs and support more creative play activities that embody the imagination of the child.
Best Paper Nomination